Answer:
-1059
Step-by-step explanation:
Katelyn, this is super easy to understand.
Anyways, to find the 96th term of the sequence, first subtract -14 and -3. You may be thinking it is -17, but it is not. -17 is only if you are subtracting -14 and 3.
(-14) - (-3) = -14 + 3 = -11.
That means the difference between each number is -11.
Now all you have to do is take the -11 and multiply it by 96, which is -1056. Then, add the -1056 to -3, which is -1059. That should be your answer.
Your school may have taught you a different way, but this is my way.
Answer:
True
Step-by-step explanation:
Answer:
Step-by-step explanation:
1) y = 50x + 2500
2) y = 200x + 1000
if we build a system with the two equations, we have:
50x+2500 = 200x + 1000
150x = 1500
x = 10
y = 2000 + 1000 = 3000
3) 10
4) $3000
Answer:
wasgood
Step-by-step explanation:
B if you need an explain I can do it